Aligning categories of mental health conditions with intervention types in high-performance sports: a narrative cornerstone review and classification framework - Lundqvist, C.; Schary, D. P.; Jacobsson, J.; Korhonen, L.; Timpka, T. (Journal of Science and Medicine in Sport, 2024)
Epidemiological studies suggest that psychiatric disorders are as prevalent among high-performance athletes as in general populations, challenging the myth of invulnerability. Despite efforts of sports organisations to highlight the significance of athletes' mental health, it is still many times tough to combine the sports performance ethos with a discourse on mental health. This narrative cornerstone review examines challenges related to definitions and classifications of athlete mental health in high-performance sports and how these influence assessments and the implementation of interventions. We discuss challenges with concept creep and psychiatrisation and outline their consequences for sports healthcare professionals. Based on this, we present a framework that aligns different categories of athlete mental health conditions (from the reduction of wellbeing to psychiatric disorders) with intervention types (from the provision of supporting environments to pharmacotherapy). We conclude that researchers and sports practitioners need to carefully consider conceptual creep and the risk of pathologising normal and healthy, albeit emotionally aversive, reactions to athlete lifeworld events when assessing athlete mental health. A clear separation of terminology denoting the athlete's resources to handle the lifeworld (including salutogenic factors) and terms describing psychiatric conditions and their management is necessary to avoid misguidance in intervention planning.